What determines immigrant caregivers' adherence to health recommendations from child primary care services? - Mourão, S. (2019)
Aim To investigate the diversity and specificity of the determinants of immigrant caregivers' adherence to child primary care (CPC) health recommendations.Background Immigrant caregiver's adherence to CPC health recommendations is of utmost importance to minimize their children's health-related vulnerabilities. Some research has been conducted on the determinants of immigrants' access to health services, but much less is known about the determinants of their adherence to health professionals' recommendations once they get there, especially in a primary health care context. This study contributes to bridge these gaps.Methods Interviews and focus groups were conducted, with immigrant and non-immigrant caregivers living in Portugal (n=35), from heterogeneous socioeconomic backgrounds. Focus group and individual interview scripts were developed to explore caregivers' understanding and use of CPC services and, particularly, their adherence to CPC recommendations. A socio-demographic questionnaire was also administered. Qualitative data were analyzed using a grounded theory methodology.Findings 'Adherence to CPC health recommendations' is a core and multidimensional concept. Several determinants were identified at individual, interpersonal, organizational and structural levels. Some determinants were highlighted both by immigrant and non-immigrant caregivers: Valuing children's health, usefulness of recommendations, perceived health-care professionals' competence, central role of vaccination in CPC and caregivers' socio-economic conditions. Other determinants were specifically mentioned by immigrant caregivers: Expectations about traditional versus pharmacological treatments, cultural mismatches in children's care practices, perceived quality of Portuguese CPC services versus CPC from countries of origin. These results provide innovative theoretical and empirical contributions to the field of primary health care and, particularly, to immigrant caregivers' adherence behaviors. Implications for research on treatment adherence in primary care contexts, the development of interventions that promote caregivers' adherence to CPC health recommendations and for child protection will be discussed.